Política e religião : participação política dos católicos carismáticos do Brasil - Reis, Marcos Vinícius de Freitas (2016)
The objective of this study is to analyze the political and partisan behavior of politicians linked to the Catholic Charismatic Renewal (CCR). The choice of this religious segment is due to the reasonable number of politicians elected to the executive and legislature and one of the most significant Catholic Catholicism sectors. Our central question is to understand the reasons for which this movement enters the Brazilian political scene and how established your support for politicians. We raise advertising material, newspaper articles and carrying out semi-structured interviews with politicians, priests, coordinators and participants.